2002
DOI: 10.1164/rccm.2112059
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pulmonary Mechanics with Increasing Disease Severity in Children and Young Adults with Cystic Fibrosis

Abstract: As forced expiratory volume in 1 second (FEV(1)) is a major predictor of outcome in patients with cystic fibrosis (CF), we investigated the effect of FEV(1) on pulmonary mechanics in children and young adults with CF. We measured respiratory rate; tidal volume; minute ventilation; arterial blood gases; sniff esophageal pressure; dynamic lung compliance; total pulmonary resistance; intrinsic positive end expiratory pressure; and total, elastic, and resistive work of breathing in 32 patients (FEV(1) range: 12-49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
3
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 27 publications
5
83
3
8
Order By: Relevance
“…In addition, children demonstrate greater 'elasticity' of lung function, which declines over time. 29 As patients with CF age and the disease progresses, repeated infections and chronic P. aeruginosa infection lead to lung damage and permanent loss of lung function, which may also reduce their capacity to respond to treatment. Interestingly, in our study those with more severe disease seemed to achieve greater improvements in lung function (as measured by the change in percent-of-predicted FEV 1 from baseline) after treatment with tobramycin than those with less severe disease (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, children demonstrate greater 'elasticity' of lung function, which declines over time. 29 As patients with CF age and the disease progresses, repeated infections and chronic P. aeruginosa infection lead to lung damage and permanent loss of lung function, which may also reduce their capacity to respond to treatment. Interestingly, in our study those with more severe disease seemed to achieve greater improvements in lung function (as measured by the change in percent-of-predicted FEV 1 from baseline) after treatment with tobramycin than those with less severe disease (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified that FEV 1 and FVC were associated only modestly with τ in CF. The relatively modest association of τ with FEV 1 and FVC implies that high values of τ and possible respiratory failure are determined by additional factors other than spirometry. Thus, τ might be conveying information that is not readily available through other methods, and has the potential to fit an unmet clinical need in managing patients with CF.…”
Section: Inspiratory Muscle Relaxation In Cf Articlesmentioning
confidence: 99%
“…Determinants of respiratory muscle compromise in CF have been reported in detail (1)(2)(3)9,19,20). Airway obstruction impacts on inspiratory muscle function by increasing the load against which the respiratory muscles are forced to operate (1) and hyperinflation places the respiratory muscles in mechanical disadvantage (2).…”
Section: Inspiratory Muscle Relaxation In Cf Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the fibrotic lung becomes progressively stiffer due to the deposition of collagen in the tissues [7]. This reduces lung volume and increases the work of breathing [8]. Nevertheless, the derangements in lung mechanics at the organ level accompanying emphysema [9] and fibrosis [10] are not simply determined by the amount of tissue loss or remodeling.…”
Section: Introductionmentioning
confidence: 99%